2019
DOI: 10.1111/obr.12934
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antidepressant and antipsychotic use on weight gain: A systematic review

Abstract: Weight gain is an adverse effect of antidepressants and antipsychotics. This side effect can lead to numerous comorbidities and reduces life expectancy. The use of these drugs is increasing worldwide, and the weight gain produced by them represents a common clinical challenge. The goal of this systematic review was to evaluate the potential association of antidepressant and antipsychotic therapy with body weight gain in cohort studies. A search of cohort studies investigating the association between weight gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 38 publications
(180 reference statements)
0
52
0
1
Order By: Relevance
“…Health care providers should also keep in mind that individuals with depression, in many cases, are on antidepressant and/or antipsychotic treatment that can lead to weight gain. 34 Thus, the interaction of depression and obesity is complex and might be more pronounced among MI survivors. So it is critically important to develop appropriate interventions to decrease the higher BMI among MI survivors with depression for improved health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Health care providers should also keep in mind that individuals with depression, in many cases, are on antidepressant and/or antipsychotic treatment that can lead to weight gain. 34 Thus, the interaction of depression and obesity is complex and might be more pronounced among MI survivors. So it is critically important to develop appropriate interventions to decrease the higher BMI among MI survivors with depression for improved health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 13% of patients prescribed paroxetine reported > 7% weight gain after a 9‐month follow‐up (69). Moreover, a retrospective cohort study observed a mean weight gain of + 2.49 kg in patients prescribed paroxetine at a 2‐year follow‐up (70,73). In a cross‐sectional study, paroxetine was associated with weight gain of 7% or more compared with baseline in over 50% of participants and a weight gain of 20% or greater in 10% of patients ( n = 80) (71).…”
Section: High‐risk Agents For Antidepressant‐induced Weight Gainmentioning
confidence: 99%
“…In der gleichen Meta-Analyse sah man Gewichtszunahmen für die meisten betrachteten Antidepressiva im ersten halben Jahr der Therapie, mit Citalopram begann die Gewichtszunahme allerdings erst nach den ersten sechs Monaten der Therapie [7]. In einer neuen Übersichtsarbeit wird der gewichtssteigernde Effekt der Antidepressiva allgemein mit einer Zunahme von etwa 5 % des initialen Körpergewichts angegeben und die Bedeutung der langjährigen Therapie für die Gewichtszunahme betont [25]. Die gewichtssteigernden Effekte von Antidepressiva können im Wesentlichen durch die gleichen Mechanismen wie bei den Neuroleptika erklärt werden.…”
Section: Antidepressivaunclassified